Successful retreatment with erlotinib after erlotinib-related interstitial lung disease - ADLI, MUSTAFA (SAGE PUBLICATIONS LTD, 2021)
Background: Epidermal growth factor receptor tyrosine kinase inhibitors are effectively being used in the treatment of non-small cell lung cancer. Although most of their adverse effects are mild to moderate, they occasionally can cause life-threatening interstitial lung disease. We aimed to present a case of lung adenocarcinoma successfully re-treated with erlotinib after recovery with effective treatment of erlotinib-induced interstitial lung disease. Case description: A 54-year-old nonsmoking woman was diagnosed with metastatic adenocarcinoma of the lung. After progression with first-line chemotherapy, erlotinib 150 mg daily was initiated. On the 45th day of erlotinib treatment, interstitial lung disease occurred and erlotinib was discontinued. Clinical improvement was achieved with dexamethasone treatment and erlotinib was re-initiated. Ten weeks after re-initiation of erlotinib, 100 mg daily partial response was observed. Conclusions: Incidence of interstitial lung disease is higher in men, smokers, and patients with pulmonary fibrosis. Interstitial lung disease radiologically causes ground-glass opacity and consolidation. The physician should quickly evaluate new respiratory symptoms in patients treated with epidermal growth factor receptor tyrosine kinase inhibitors, discontinue the epidermal growth factor receptor tyrosine kinase inhibitor treatment, and initiate corticosteroids if clinical diagnosis is interstitial lung disease.
Keywords: Epidermal growth factor receptor; interstitial lung disease; lung neoplasms; CANCER PATIENTS